Improving testicular examinations on paediatric patients in the emergency department: A quality improvement study to improve early diagnosis of testicular torsion - Ernest M. Cheng; Juanita N. Chui; Murray Crowe; Andrew Cooke (Asian Journal of Urology)
Objective: Male paediatric patients presenting with abdominal and/or testicular pain are common in the emergency department. As a time-sensitive diagnosis, the importance of early recognition, referral, and definitive management is critical. Missed or delayed diagnoses and management of testicular torsion can result in significant long-term sequelae including impaired fertility and psychological burden. In this quality improvement study, we utilised educational posters aiming to improve awareness of testicular torsion as a differential for abdominal pain and therefore, improve the quality of testicular examinations performed in the emergency department. Methods: Observational pre- and post-intervention study was conducted at a tertiary hospital emergency department. A pre-interventional retrospective review of the electronic medical records was conducted. All male patients under 16-years-old presenting with “abdominal pain” or “testicular problem” were included. We assessed the rate of testicular examination and the quality of the examination based on four domains: Cremasteric reflex, lie, swelling, and hardness. Educational posters targeting both patients and clinicians were placed around the emergency department. Subsequent review of the electronic medical records post-intervention was performed assessing the same domains. Results: A total of 235 presentations were analysed with 124 in the pre-intervention group and 111 in the post-intervention group. Overall rate of documented testicular examinations increased by 14% (p=0.032). The quality of testicular examinations also improved from an average of 0.85 domains documented to 2.29 post-intervention (p<0.001). Subgroup analysis found doctors in training had a greater improvement in both rate and quality of documented testicular examination. Conclusion: Our study demonstrated the value of continuing education in promoting awareness of testicular torsion in the emergency department. We found a clear improvement in the quality of clinical documentation of a time-sensitive condition which may infer a decreased risk of missed and delayed diagnosis of testicular torsion.